2021
DOI: 10.1080/14737175.2021.1890033
|View full text |Cite
|
Sign up to set email alerts
|

A critical evaluation of midazolam nasal spray for the treatment of patients with seizure clusters

Abstract: Introduction: Patients with epilepsy may experience seizure clusters (SCs), which are considered a medical emergency requiring immediate treatment. Besides seizures and seizure-related injuries, patients with SCs experience impaired quality of life and have a greater need for healthcare resources. Midazolam nasal spray (MDZ-NS) was approved by the United States Food and Drug Administration (FDA) for the treatment of SCs in 2019, and was the first FDA-approved nasally administered formulation for treating SCs.A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 48 publications
0
14
0
2
Order By: Relevance
“…Most concentrated intranasal solutions have an acidic pH, which can cause nasal irritation, discomfort, and less reliable absorption of midazolam [9,14,35,36]. The solubility of MDZ was greatly increased by decreasing the pH from near-physiological values to pH 3.3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most concentrated intranasal solutions have an acidic pH, which can cause nasal irritation, discomfort, and less reliable absorption of midazolam [9,14,35,36]. The solubility of MDZ was greatly increased by decreasing the pH from near-physiological values to pH 3.3.…”
Section: Discussionmentioning
confidence: 99%
“…Benzodiazepines (diazepam and midazolam) are the most commonly used, first-line drugs for the management of acute seizures [4,7,8]. Buccally administered midazolam (BC-MDZ) and rectally administered diazepam are recommended for treating seizure clusters in several authoritative guidelines in China, and they are licensed in the European Union [9,10]. As a result of the disadvantage of inconvenient use of the rectal preparation [10] and the buccal route of administration often being hampered by jaw clenching, hypersalivation, or uncontrolled swallowing [11], which limits their use in the acute setting [12], a nasal spray was developed for both drugs and approved by the US Food and Drug Administration (FDA) in 2019 and 2020, respectively [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, in such cases, the intranasal route is beneficial because it is painless, noninvasive, and easy to access [14,15]. But the intranasal route in nasal solution form is not standardized, and local irritation may occur because of the acidic solution (2.8-3.0 pH), and the small volume of the nasal cavity requires high doses, which leads to a significant first-pass effect and decreased bioavailability and efficacy [16][17][18]. So, the development of nasal spray formulation (midazolam nasal spray {MDZ-NS}) became a promising alternative in emergency cases as rescue medication where other routes are not feasible.…”
Section: Introductionmentioning
confidence: 99%
“…So, the development of nasal spray formulation (midazolam nasal spray {MDZ-NS}) became a promising alternative in emergency cases as rescue medication where other routes are not feasible. It is also observed that the metabolic compound of midazolam nasal spray (MDZ-NS) to MDZ ratio for MDZ-NS is lower than oral MDZ, demonstrating that intranasal administration avoids first-pass metabolism [16][17][18].…”
Section: Introductionmentioning
confidence: 99%